The complete mitochondrial genome of Poncelet’s giant rat (Solomys ponceleti) from the Solomon Islands Archipelago - Andrew G. King; Sandy Ingleby; Matthew J. Lott; Kristofer M. Helgen; Mark D. B. Eldridge; David E. Alquezar-Planas (Mitochondrial DNA. Part B. Resources, 2025)
Poncelet’s giant rat (Solomys ponceleti Troughton 1935), is a rare, large murine rodent that is endemic to the Solomon Islands Archipelago in the southwest Pacific Ocean. The species is only known from the adjacent islands of Bougainville and Choiseul and is the largest member of the genus. Here, we describe the complete mitochondrial genome of S. ponceleti and compare it to other Rodentia. The S. ponceleti circular mitogenome was 16,246 bp and contained 13 protein-coding genes, two rRNA genes, 22 tRNAs, and a control region (D-loop). Phylogenetic analysis of selected, published mitogenomes reveals a close relationship to other Australo-Papuan murine rodents.